Os projetos sociais do povo indígena Xakriabá e a participação dos sujeitos: entre o 'desenho da mente', a 'tinta no papel' e a 'mão na massa' - Suzana Alves Escobar (2012)
The scope of this thesis is to describe and analyze the practices of associativism of the Xacriabá people focusing on the subjects participation in the elaboration, implementation and administration of social projects, process also mediated by both oral and written languages. Have been considered as categories of analysis: meetings, as places where activities are developed, relations of power, mediations external to the communities - that of the contact with external agents -, and the written language. Methodology includes ethnographic research, which attempted to reveal, during social practices, the forms of participation of the subjects involved in social projects. Culture and identity were discussed and issues involving literacy, oral and written languages were analyzed. During the investigation with the associations, specifically with the Barreiro Preto village and the organization of the Grupos de Roça, it was possible to study and analyze the experience with associativism and social projects. The conclusion is that associativism marked local history substantially. It became patent as well that the subjects forms of participation is defined from the conceptions engendered in the relations of local power, among others, and that such concepts themselves are part of the movement provoked by associativism and social projects. Another important aspect of the investigation is the way the Xakriabá make use of the written culture during activities related to the social projects, which ended up by inspiring the subtitle of this thesis, i. e.: the demand transformed into a project is firstly designed in the minds and then discussed in the groups selected through the mobilization of the local participants or/and partners who are able to make use of the written language as an alphabetical notation to, later, make it result in a formatted document, ink on paper, so to speak, to be finally materialized as such with the effective overall participation of the people involved in the process.